2015
DOI: 10.1007/s00464-015-4177-y
|View full text |Cite
|
Sign up to set email alerts
|

One- and ten-year outcome of laparoscopic anterior 120° versus total fundoplication: a double-blind, randomized multicenter study

Abstract: Both procedures offer good long-term control of reflux symptom, with modest post-fundoplication symptoms. Anterior 120° fundoplication results in less dysphagia, better ability to belch and vomit than total fundoplication at 10-year follow-up. The results suggest that APF could be an alternative to Nissen fundoplication in the surgical treatment of mild-moderate GERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Almost 25% of our patients were using acid‐suppression medication 10 years after surgery. Previous studies have reported long‐term post‐operative acid‐suppression medication to range between 5.8% and 62% . In our study, 32% of the patients who were interviewed 20 years after surgery about the reason for taking acid‐suppression medication, reported only mild reflux symptoms or reasons not related to reflux.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Almost 25% of our patients were using acid‐suppression medication 10 years after surgery. Previous studies have reported long‐term post‐operative acid‐suppression medication to range between 5.8% and 62% . In our study, 32% of the patients who were interviewed 20 years after surgery about the reason for taking acid‐suppression medication, reported only mild reflux symptoms or reasons not related to reflux.…”
Section: Discussionmentioning
confidence: 51%
“…Improvement in QoL after laparoscopic fundoplication for GERD has been shown using both instruments . Other studies have used the Gastrointestinal Symptom Rating Scale alone or in conjunction with the Psychological General Wellbeing Index . The Gastrointestinal Symptom Rating Scale was initially developed for irritable bowel syndrome and peptic ulcer, whereas the Psychological General Wellbeing Index is a measure of subjective well‐being .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both cases, the research question and the aim of the study are set forth more or less implicitly as well as the design used (a SR). "One-and ten-year outcome of laparoscopic anterior 120° versus total fundoplication: a double-blind, randomized multicenter study" (Djerf et al, 2016): this example expresses the aim of the study as well as the design used (a RCT).…”
Section: The Titlementioning
confidence: 99%